COAGULOPATHY AND CORONAVIRUS DISEASE 2019 - Aleksić, Sanja (Acta medicae Medianae, 2025)
Interest in coronavirus disease 2019 (COVID-19) in the world of science is constant. Pathogenesis is the subject of many studies, and coagulopathy occupies an important place in research. In our study, blood samples were collected from 131 patients treated for SARS-CoV-2 infection in University Clinical Center Kragujevac. Blood was sampled on the day of admission, and the disease course was monitored. We concluded that our participants do not meet the criteria for disseminated intravascular coagulation (DIC). We showed the statistical significance of platelet count, prothrombin time value and DIC score concerning the form and outcome of the disease. Patients with a critical form of the disease, as well as those who died, had significantly lower values of the number of platelets and significantly higher values of the DIC score.
Keywords: coronavirus disease, disseminated intravascular coagulation, disease form, disease outcome